2010
DOI: 10.4021/jocmr447w
|View full text |Cite
|
Sign up to set email alerts
|

Inappropriate Use of Intravenous PPI for Stress Ulcer Prophylaxis in an Inner City Community Hospital

Abstract: BackgroundProton pump inhibitors (PPIs) are used for the treatment and prophylaxis of variety of acid peptic conditions including stress ulcers. There has been a persistent practice of their inappropriate use for stress ulcer prophylaxis. Purpose of our study was to measure the inappropriate use of Intravenous Proton Pump Inhibitors for stress ulcer prophylaxis and to estimate the financial burden.MethodsWe carried out a retrospective, analytic study from July 2008 to June 2009 in internal medicine department.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 8 publications
0
8
0
Order By: Relevance
“…An enormous drug cost burden on patients and insurances relates to inappropriate PPI administration for SUP purposes . Clinical pharmacist participation in patient management may decrease SUP‐related expenditures without having a detrimental impact on quality of care . In the present study, pharmacists' intervention reduced relative the SUP cost by about 70%.…”
Section: Discussionmentioning
confidence: 59%
“…An enormous drug cost burden on patients and insurances relates to inappropriate PPI administration for SUP purposes . Clinical pharmacist participation in patient management may decrease SUP‐related expenditures without having a detrimental impact on quality of care . In the present study, pharmacists' intervention reduced relative the SUP cost by about 70%.…”
Section: Discussionmentioning
confidence: 59%
“…However, the proportion of inappropriate SUP prescription in this study was less than what was reported in other studies, which indicated 60%–80% of inappropriate SUP use. 19,2629 This difference may be because our study was conducted at a teaching hospital where standard guidelines may be better practiced. Our claim was supported by many studies which revealed SUP usage in academic centers was more compliant with the guidelines than nonacademic hospitals.…”
Section: Discussionmentioning
confidence: 99%
“…The result of this study is in agreement with previous reports. 27,3336 According to Farsaei et al, 19 70.3% of patients received SUP when it was not indicated. In addition, overuse of AST in non-critically ill patients has been reported by several investigators.…”
Section: Discussionmentioning
confidence: 99%
“…High morbidity and mortality of stress ulcer-related bleeding and concerns about cost and adverse effects of SUP administrations such as pneumonia and Clostridium difficile infections, provoked different studies to determine the pattern of SUP prescription in ICU and non-ICU patients. [ 2 3 4 5 6 7 8 9 10 11 12 13 ]…”
Section: Introductionmentioning
confidence: 99%